Peran Guru Dalam Mewujudkan Lingkungan Belajar Yang Ramah Anak - Hayani Wulandari; Denisa Putri Rahmawan (Peneliti.net, 2023)
Cases of bullying is one of the problems that often occur today. The perpetrators of bullying do not only come from adults, even children are also perpetrators as well as victims. This research uses qualitative methods with descriptive analysis techniques with library research or literature studies. The purpose of this study is to find out cases of bullying that occur in Early Childhood Education (PAUD) and Kindergarten (TK) and the role of teachers in creating a child-friendly learning environment. Bullying can have a bad impact. Bullying in early childhood at school can cause children not wanting to go to school. Children who are victims of bullying feel that school is not a safe place. As a result, victims feel inferior and can even lead to depression from an early age. For the perpetrators of this behavior can be the basis for the formation of bad character. If this continues to occur repeatedly in early childhood, it will certainly have a negative impact on the child's social, emotional and physical development